Effects of fixatives on stable isotopes of fish muscle tissue: implications for trophic studies on preserved specimens. Issue 4 (21st February 2020) - Durante, L. M.; Sabadel, A. J. M.; Frew, R. D.; Ingram, T.; Wing, S. R.
Abstract: Isotopic ecology has been widely used to understand spatial connectivity and trophic interactions in marine systems. However, its potential for monitoring an ecosystem's health and function has been hampered by the lack of consistent sample storage and long‐term studies. Preserved specimens from museum collections are a valuable source of tissue for analyses from ancient and pre‐modern times, but isotopic signatures are known to be affected by commonly used fixatives. The aim of the present study was to understand the effects of fixatives on isotopic signatures of bulk tissue (δ 13 Cm and δ 15 Nm ) and amino acids (δ 13 CAA and δ 15 NAA ) of fish muscle and to provide correction equations for the isotopic shifts. Two specimens of each: blue cod ( Parapercis colias ), blue warehou ( Seriolella brama ), and king salmon ( Oncorhynchus tschawytscha ) were sampled at five locations along their dorsal musculature, at four time periods: (1) fresh, (2) after 1 month preserved in formalin, and after (3) 3 and (4) 12 months fixed in either ethanol or isopropanol. Lipid content was positively correlated with C:N ratio ( r ² = 0.83) and had a significant effect on δ 13 C after treatments, but not on δ 15 N. C:N ratio (for δ 13 Cm ) and percent N (for δ 15 Nm ) from preserved specimens contributed to the most parsimonious mixed models, which explained 79% of the variation due to fixation and preservation for δ 13 C and 81% for δ 15 N. δ 13 CAA were generally not affected by fixatives and preservatives, while most δ 15 NAA showed different signatures between treatments. δ 15 NAA variations did not affect the magnitude of differences between amino acids, allowing scientists to retrieve ecological information (e.g., trophic level) independently of time under preservation. Corrections were applied to the raw data of the experiment, highlighting the importance of δ 13 Cm and δ 15 Nm correction when fish muscle tissues from wet collections are compared to fresh samples. Our results make it possible to retrieve δ 13 Cm, δ 15 Nm, δ 13 CAA, and δ 15 NAA from museum specimens and can be applied to some of the fundamental questions in ecology, such as trophic baseline shifts and changes in community's food web structure through time.